Перспективи: Автоматизації вимірювання умов у житлових та робочих приміщеннях з використанням комп’ютерно-інтегрованих рішень - Халімонов, Я. І. (ХНУРЕ, 2023)
This article provides overview of modern modules for automated measurement of conditions in living and working premises. The need for use of automated systems, relevance of their use, both for private homes and for corporate spaces, is considered. Four basic perspectives are highlighted: automation of conditions measurement in living and working premises using computer-integrated solutions.
Perspectives: automation of measuring conditions in residential and working premises using computer-integrated solutions
Keywords: автоматизація вимірювань; житлові приміщення; робочі приміщення